Evaluation of the Antiproliferative Activity of 2-(Monohalogenophenylamino)-5-(2,4-dihydroxyphenyl)-1,3,4-thiadiazoles - Juszczak, Matgorzata; Matysiak, Joanna; Brzana, Wojciech; Niewiadomy, Andrzej; Rzeski, Wojciech (Arzneimittelforschung, 2008)
Two 2-(monohalogenophenylamino)-5-(2,4-dihydroxyphenyl)-1,3,4-thiadiazoles were synthesized by reaction of sulfinyl bis(2,4-dihydroxythiobenzoyl) with 4-substituted 3-thiosemicarbazides and evaluated for their antiproliferative activity in tumor cells and for cytotoxicity in normal cells. Both derivatives in micro-molar concentrations elicited a prominent antiproliferative effect in tumor cells derived from cancers of the nervous system (rhabdomyosarcoma/medulloblastoma, glioma) and peripheral cancers, including breast adenocarcinoma and lung carcinoma. The anticancer effect was attributed to decreased DNA synthesis and was not connected with apoptosis induction. Both compounds were not toxic to normal human skin fibroblasts.
Keywords: 2-Amino-5-(2,4-dihydroxy-phenyl)-1,3,4-thiadiazoles, antiproliferative activity; apoptosis, cytotoxicity; Anticancer agents